Google SketchUp and Lumion Based Marine Tourism Destination Development Design - et. al., Husain Syam, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to describe the design of marine tourism development based on Google SketchUp and Lumion. The research location is on the island of Larea-rea as one of the marine tourism development destinations in the East Coast Region of South Sulawesi Province, Indonesia. This type of research is Research and Development (R&D) by applying the ADDIE (Analysis, Design, Development, Implementation and Evaluation) Approach. The data collection techniques used were field studies, observations and interviews. Data analysis was carried out following the stages of data collection, data condensation, data presentation, verification / concluding. The results showed that the design of tourism destination development carried out following the concept of ecotourism. This reality is shown in the empowerment of miniature mangrove forests to prevent coastal abrasion and the use of local cultural themes where the design of the roof side of the Rumah Sembilan is used according to the Karampuang traditional house. At the research locus, it can be seen that the natural marine potential possessed by the island of Larea-rea is still natural and well maintained in the form of unpolluted white sand beaches with clear seawater and natural coral reef conditions to support the development of ecotourism-based tourism.